The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/ijbpa-02-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of additional insulation of building façades in Sweden

Abstract: Purpose The purpose of this paper is to evaluate long-term effects of previous policies for energy efficiency on energy performance and heritage values. A further ambition is to better understand the relationship between energy and preservation by exploring a quantitative method of combining energy performance data with official heritage designation. Design/methodology/approach The study is based on a quantitative analysis of energy performance, completed additional insulations, and official heritage classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In Sweden, building conservation has had to step aside for policies ultimately designed to boost IJBPA 38,4 the level of employment in the building sector and to upgrade the housing stock (Tunefalk and Legn er, 2019a). A study of Arsta (a district of multi-family buildings built in the 1940s) in Stockholm showed that façade insulation improved energy efficiency considerably, while at the same time, permanently diminishing the architectural values and thus giving the buildings weaker legal protection (Tunefalk and Legn er, 2019b). Even when carried out in a seemingly sensitive way and according to guidelines, thermal insulation of facades has diminished the architectural values of even modern buildings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Sweden, building conservation has had to step aside for policies ultimately designed to boost IJBPA 38,4 the level of employment in the building sector and to upgrade the housing stock (Tunefalk and Legn er, 2019a). A study of Arsta (a district of multi-family buildings built in the 1940s) in Stockholm showed that façade insulation improved energy efficiency considerably, while at the same time, permanently diminishing the architectural values and thus giving the buildings weaker legal protection (Tunefalk and Legn er, 2019b). Even when carried out in a seemingly sensitive way and according to guidelines, thermal insulation of facades has diminished the architectural values of even modern buildings.…”
Section: Literature Reviewmentioning
confidence: 99%